Hubungan Tingkat Pengetahuan Dengan Motivasi Melaksanakan Diet Pada Pasien Diabetes Melitus Rawat Jalan Di Rsud Dr. Moewardi - Zahrok, Fatimatuz; , Luluk Ria Rakhma,S.Gz.,M.Gz; , Nur Lathifah M, S.Gz, MS (2015)
Background: Diabetes mellitus is a degenerative disease whose victims always increase every year including in Indonesia, this is caused by a lack of knowledge about diabetes mellitus and unhealthy lifestyle including unhealthy diet and lack of exercise. Knowledge and motivation in carrying out diabetes mellitus diet are also factors contributing to diabetes mellitus. Objective: The purpose of this study was to determine the relationship between patient's knowledge and the implementation of motivation to apply diabetes mellitus diet in diabetes mellitus patients at Dr. Moewardi Hospital of Surakarta. Research Method: The research was an observational with cross-sectional study design. The number of respondents in this study were 57 patients which were selected through sequential random sampling. The data were collected through interview using a questionnaire. The statistical test used to analyzed the relationship between variables were Pearson Product Moment tests. Results: The results showed that most respondents had good knowledge (63,2%) and good diabetes mellitus diet motivation (89,5%). The relationship between patients knowledge and the motivation in carrying out diet diabetes mellitus diet in diabetes mellitus patients had p value (p) of 0,133. Conclusion: The results of the analysis of the data showed that there was no significant correlation between patient's knowledge and the motivation in carrying out diabetes mellitus diet in diabetes mellitus patients at Dr. Moewardi Hospital of Surakarta